The Idealist Philosophers’ God - Armour, Leslie (Laval théologique et philosophique, 2002)
AbstractThis paper argues that there are still clues in the ideas of Ralph Cudworth that enable us to develop a philosophical concept of God capable of addressing many of the perplexities of our own time. The association of love with the ultimately real emerges in Cudworth as a viable philosophical idea. It is argued further that the only successful idealist philosophy of religion is one which makes goodness paramount, and that only its concrete manifestation as love can make the notion of God intelligible, as can be seen today in the works of Jean-Luc Marion.